Applying for research funding getting started and getting funded - Ries, Joanne B.; Leukefeld, Carl G.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1995)
Designed to help the researcher approach the grant application process & develop a competitive & successful application, this text leads the reader through the process step by step, highlighting the important elements.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Research grants; Grants-in-aid.; Proposal writing for grants; Electronic books